Clinical and pharmacological correlates of caffeine consumption in subjects with schizophrenia – Data from the FACE-SZ cohort. (May 2023) - Szoke, Andrei; Richard, Jean-Romain; Fond, Guillaume; Misdrahi, David; Lajnef, Mohamed; Aouizerate, Bruno; Boyer, Laurent; Berna, Fabrice; Capdevielle, Delphine; André, Myrtille; Chereau, Isabelle; Clauss-Kobayashi, Julie; et al.
Abstract: Caffeine is the most consumed psychoactive substance worldwide. Previous studies suggested higher caffeine consumption in subjects with schizophrenia spectrum disorders (SSD) as well as associations with symptoms, medication and medication side-effects. In a large and well-characterized sample of SSD subjects we explored the association between caffeine consumption and clinical (psychosis related, severity, general health) as well as pharmacological (antipsychotic treatment, sedation potential) variables. Eight hundred four subjects with data on their caffeine (coffee and tea) consumption successively recruited were included in this study. After controlling for potential confounders (demographic variables, smoking) only the negative dimension of psychosis was associated with the amount of caffeine ingested. Less severe negative symptoms were associated with higher caffeine consumption. The effect size of this association was small (partial correlation coefficient = −0.12) but significant. Highlights: Higher caffeine consumption was associated with lower negative symptoms. This association was still significant after adjustment for multiple confounders. A more sedative treatment was associated with higher caffeine consumption. Taking into account smoking the association with treatment was no more significant. Caffeine consumption was not associated with anxiety or quality of sleep.